2014
DOI: 10.1590/s0100-06832014000100021
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter and macronutrient accumulation in fruits of Conilon coffee with different ripening cycles

Abstract: SUMMARYThe period between anthesis and fruit ripening varies according to the Conilon coffee (Coffea canephora) genotype. Therefore, the time of the nutritional requirements for fruit formation may differ, depending on the formation phase and the genotype, and may directly affect split application of fertilizer. The aim of this study was to quantify the accumulation of dry matter and N, P, K, Ca, Mg and S at several stages in the fruit of the Conilon coffee genotype with different ripening cycles, which may su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
72
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 18 publications
13
72
1
5
Order By: Relevance
“…This result was certainly associated with the grain formation stage of the coffee plants, when the requirement for nutrients is high. As fruits constitute preferential sinks for nutrients and photoassimilates (Laviola et al, 2008;Partelli, Espindola, Marré, & Vieira, 2014), vegetative growth is severely jeopardized during this stage, due to an accentuated imbalance in the source:sink ratio of these productive branches, despite these branches (PlagBB) possessing limited autonomy in the production and supply of carbohydrates, as verified for C. arabica (Chaves, Martins, Batista, Celin, & DaMatta, 2012). Additionally, the advent of new branches (budding) may reduce the growth of older branches (Ferreira et al, 2013) due to the changes in the source:sink relationship among different branches.…”
Section: Resultsmentioning
confidence: 99%
“…This result was certainly associated with the grain formation stage of the coffee plants, when the requirement for nutrients is high. As fruits constitute preferential sinks for nutrients and photoassimilates (Laviola et al, 2008;Partelli, Espindola, Marré, & Vieira, 2014), vegetative growth is severely jeopardized during this stage, due to an accentuated imbalance in the source:sink ratio of these productive branches, despite these branches (PlagBB) possessing limited autonomy in the production and supply of carbohydrates, as verified for C. arabica (Chaves, Martins, Batista, Celin, & DaMatta, 2012). Additionally, the advent of new branches (budding) may reduce the growth of older branches (Ferreira et al, 2013) due to the changes in the source:sink relationship among different branches.…”
Section: Resultsmentioning
confidence: 99%
“…Australian cedar exhibits rapid growth and high-quality wood and can be used together with coffee to diversify production, distributing the economic return over the year and providing a better utilization of the area (Müller et al, 2004). Coffee is often subjected to supra optimal temperatures that sometimes exceed 38 ºC during the critical grain filling phase (Partelli et al, 2010;2014b). These conditions, coupled with the occurrence of strong winds and high rates of evapotranspiration, can be stressful to the crop, requiring different management techniques to mitigate these problems (Partelli et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their allogamy, plants of seminiferous origin are highly heterogeneous, exhibiting high morphological and genetic diversity (Conagin and Mendes, 1961;Bragança et al, 2001). However, propagation through cutting has been used for many years because it has several advantages, such as the retention of genetic characteristics of the stock plant, greater crop homogeneity, increased productivity, and the ability to separate crops based on their maturation cycle (Bragança et al, 2001;Partelli et al, 2014b). Genetic variability in the population is required for any genetic improvement program because it allows the selection of superior genotypes (Ivoglo et al, 2008) that are adapted to the soil and climate conditions of the cultivation region.…”
Section: Introductionmentioning
confidence: 99%
“…Denoeud et al (2014) found C. canephora to be a useful reference species for understanding the evolution of genomic structure in asterid angiosperms. Genotypes of Conilon coffee exhibit countless differences, including polyclonal varieties (Fonseca et al, 2004), a group of clones that are generally grouped by maturation cycle: early, medium, late and very late (Partelli et al, 2014b). A physiologically viable cutting method has been developed, guaranteeing the maximum homogeneity of fields, particularly in grain maturation, among other desirable characteristics (Weigel and Jurgens, 2002;Paiva et al, 2012;Partelli et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%